Avaliação da influência dos parâmetros de processamento na manufatura aditiva do aço VP50IM por arco elétrico a gás - Toaldo, Paulo Henrique (2022)
Welding processes such as mechanical fabrication are essential in producing and repairing components for most manufacturing industries. Furthermore, in recent years the demand for wire arc additive manufacturing (welding process known as WAAM, (Wire Arc Additive Manufacturing) has increased, becoming an alternative to subtractive manufacturing, which has a significant loss of material. In the WAAM process, multilayer deposition of weld beads is used following a digital model, producing a threedimensional mechanical structure. The use of additive manufacturing is recognized for manufacturing parts of high geometric complexity and repairing components with mechanical properties comparable to the cast material. However, there are significant challenges associated with WAAM, such as undesirable microstructures and mechanical properties, high residual stresses, and geometry distortion. In this context, this study contributes to the topic with a parameter selection methodology for WAAM using pulsed GTAW (Gas Tungsten Arc Welding) and the characterization of the generated stacking. The CCC methodology (Complete Composite Central) was used to evaluate the definition of additive manufacturing parameters. Peak current (Cp), base current (Cb), peak current wire feeding speed (Vap), base current wire feeding speed (Vab), and welding speed (Vs) were evaluated. The parameters selection methodology evidenced schematics logic for a viable choice of definition parameters for additive manufacturing. The ideal parameters were Cp=200A, Cb=100A, Vap=2.9cm/min, Vab=1.2cm/min, and Vs=20cm/min. Tests were performed on robustness, durability, visual attraction, microstructure, and crosssection geometry of samples configured in additive manufacturing in the ideal parameter designed ideally. The transverse direction is transverse. Lower center tests up to 9% building durability compared to top and base hardness. The fracture analysis of the samples shows some inclusions and a ductile fracture. Standard ISO 4287 was used for roughness evaluation through the polishing test. The roughness values reached 0.265 Ra with no signs of discontinuity.